Influence of Feed Grade Amino Acid Inclusion Level in Late Nursery and Grower Diets Fed to Pigs from 21 to 75 lb - Hadley R. Williams; Mike D. Tokach; Jason C. Woodworth; Joel M DeRouchey; Robert D. Goodband; Jordan T. Gebhardt; Chad W. Hastad; Zach B. Post; Keith D. Haydon (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 912 pigs (PIC TR4 × (Fast LW × PIC L02); initially 21.4 lb) were used in a 43-d trial to evaluate the influence of feed grade amino acid in diets containing 30% dried distillers grains with solubles (DDGS) fed to pigs from 21 to 75 lb. Pigs were randomly assigned to pens (19 pigs per pen) and pens were randomly allotted in weight blocks to 1 of 4 dietary treatments with 12 pens per treatment. Dietary treatments contained low, medium, high, or very high additions of feed grade amino acids with L-lysine added at approximately 0.25, 0.40, 0.55, and 0.70% of the diet. This corresponded to 15, 24, 33, and 42% of the standardized ileal digestibility (SID) lysine coming from L-lysine. All other amino acids were added as needed to meet minimum desired ratios relative to lysine (60% Ile; 58% Met and Cys; 65% Thr; 19% Trp; and 72% Val). Predetermined orthogonal contrasts were used to evaluate linear or quadratic effects based on the feed grade lysine to total lysine ratio. Overall (d 0 to 43), there was an increase (quadratic,P<0.020) in average daily gain (ADG) and average daily feed intake (ADFI), with pigs fed increasing feed grade amino acids having increased gain and feed intake up to the high addition of feed grade amino acids and decreasing for pigs fed the very high diet. For overall feed efficiency (F/G), pigs fed the medium feed grade amino acids had improved F/G (P= 0.002) compared to pigs fed the high and very high levels of feed grade amino acids, with the pigs fed the low feed grade amino acids intermediate. As feed grade amino acids increased in the diet, blood urea nitrogen decreased (linear,P =0.001) on d 21 and 43. In summary, as the percentage of L-lysine as a proportion of total SID lysine increased in the diet from 15 (Low) to 24% (Medium), ADG and F/G improved; however, as the L-lysine as a proportion of total SID lysine in the diet increased to greater than 24%, F/G worsened.
Keywords: branch chain amino acids; growth performance; nursery